Breath-Synchronized Nebulized Surfactant in a Porcine Model of Acute Respiratory Distress Syndrome. (15th February 2021) - DiBlasi, Robert M.; Kajimoto, Masaki; Poli, Jonathan A.; Deutsch, Gail; Pfeiffer, Juergen; Zimmerman, Joseph; Crotwell, David N.; Malone, Patrik; Fink, James B.; Ringer, Coral; Uthamanthil, Rajesh; Ledee, Dolena; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Effective treatment options for surfactant therapy in acute respiratory distress syndrome and coronavirus disease 2019 have not been established. To conduct preclinical studies in vitro and in vivo to evaluate efficiency, particle size, dosing, safety, and efficacy of inhaled surfactant using a breath-synchronized, nebulized delivery system in an established acute respiratory distress syndrome model. Design: Preclinical study. Setting: Research laboratory. Subjects: Anesthetized pigs. Intervention: In vitro analysis included particle size distribution and inhaled dose during simulated ventilation using a novel breath-synchronized nebulizer. Physiologic effects of inhaled aerosolized surfactant (treatment) were compared with aerosolized normal saline (control) in an adult porcine model (weight of 34.3 ± 0.6 kg) of severe acute respiratory distress syndrome (Pao 2 /Fio 2 <100) with lung lavages and ventilator-induced lung injury during invasive ventilation. Measurements and Main Results: Mass median aerosol diameter was 2.8 µm. In vitro dose delivered distal to the endotracheal tube during mechanical ventilation was 85% ± 5%. Nebulizers were functional up to 20 doses of 108 mg of surfactant. Surfactant-treated animals ( n = 4) exhibited rapid improvement in oxygenation with nearly full recovery of Pao 2 /Fio 2 ( 300) and end-expiratory lung volumes with nominal dose less than 30 mg/kg of surfactant, whereas control subjects ( n = 3) maintained Pao 2 /Fio 2 less than 100 over 4.5 hours with reduced end-expiratory lung volume. There was notably greater surfactant phospholipid content and lower indicators of lung inflammation and pathologic lung injury in surfactant-treated pigs than controls. There were no peridosing complications associated with nebulized surfactant, but surfactant-treated animals had progressively higher airway resistance post treatment than controls with no differences in ventilation effects between the two groups. Conclusions: Breath-synchronized, nebulized bovine surfactant appears to be a safe and feasible treatment option for use in coronavirus disease 2019 and other severe forms of acute respiratory distress syndrome.